Academic psychiatry journals in South Asian countries: most from India, none from Afghanistan, Bhutan and the Maldives. Issue 1 (2022) - Arafat, S.M. Yasir; Ali, Syeda Ayat-e-Zainab; Saleem, Tamkeen; Banerjee, Debanjan; Singh, Rakesh; Baminiwatta, Anuradha; Shoib, Sheikh
No abstract available